EFEKTIFITAS TERAPI MOXA DAN HYPNOBIRTHING UNTUK PERBAIKAN LETAK SUNGSANG PADA IBU HAMIL TRIMESTER III - Dede Waslia; Nanik Cahyati (LPPM Universitas Abdurrab, 2021)
Breech pregnancy is a pregnancy with fetal abnormalities where this condition puts the mother and fetus at high risk of morbidity and mortality. The risk of breech delivery makes caesarean sections the safest way to help with childbirth. Based on Riskesdas data (2010), WHO sets the indicator of caesarean delivery 5–15% for each country, where in Indonesia 10% of Caesarean sections are performed on pregnant women with breech location. Normal labor is the desire of every pregnant woman, therefore some kind of maneuver is promoted in changing the breech position into the location of the head. Moxa therapy is a therapy done by burning mugwort potions that are compacted and rolled cylindrical and placed near the bladder acupuncture point (BL) 67 located on the outside of the little finger of the foot until it produces hyperemi from local vasodilatation, the goal of which is to help the fetal playback version. Hypnobirthing can suggest and reprogram the subconscious mind that can be directed to make changes in the mother's body. The release of fear in hypnobirthing helps the mother relax and allow her baby to spin. The purpose of this study is to find out the effectiveness of moxa and hypnobirthing therapy and the most effective methods for improving breech location in Trimester III pregnant women. The research method used is pure experimentation with post test control group design. Samples in this study as many as 33 pregnant women with gestational age of 32-37 weeks. The data analysis used is kruskall-wallis test. The results of the study found that moxa therapy and hypnobirthing are effective in improving breech location with a value of p 0.001 (p<0.05). Moxa therapy is the most effective method with a mean value (25.50). Moxa therapy recommendations are effective and safe to help the fetal screening version with breech location.